2017
DOI: 10.1115/1.4037761
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Error Due to Resonance in Synchronous Belt Drive With Eccentric Pulley

Abstract: In synchronous belt drives, it is generally difficult to eliminate pulley eccentricity, because the pulley teeth and shaft hole are produced separately and the pulley is installed on an eccentric shaft. This eccentricity affects the accuracy of rotation transmission, so that the belt tension changes during a single rotation of the pulley. This in turn affects the occurrence of resonance in the spans. In the present study, the transmission error in a synchronous belt drive with an eccentric pulley in the absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Makita et al(2004) studied theoretically and experimentally the transmission error in synchronous belt drives with an idler, and results showed that the belt thickness errors between the belt pitch line and back face of the belt was a main reason of the transmission error generated. Kagotani et al(2017) studied the transmission error due to resonance between synchronous belt drive and eccentric pulley. Kagotani et al(2012) studied the transmission errors in which the belt spans generate first mode vibration due to the resonance, and results showed that the transmission error has a period of 1/2 of one pitch of the pulley.…”
Section: Introductionmentioning
confidence: 99%
“…Makita et al(2004) studied theoretically and experimentally the transmission error in synchronous belt drives with an idler, and results showed that the belt thickness errors between the belt pitch line and back face of the belt was a main reason of the transmission error generated. Kagotani et al(2017) studied the transmission error due to resonance between synchronous belt drive and eccentric pulley. Kagotani et al(2012) studied the transmission errors in which the belt spans generate first mode vibration due to the resonance, and results showed that the transmission error has a period of 1/2 of one pitch of the pulley.…”
Section: Introductionmentioning
confidence: 99%